Current Processes for Identifying and Managing Traumatic Brain Injury (TBI) in the Justice Sector - Wilson, Lara (Auckland University of Technology, 2023)
Traumatic brain injury (TBI) is a significant health concern, with one in three people in the general population experiencing at least one TBI before age 25. The prevalence is even higher in people within the justice sector. Considering TBI can cause chronic disability, with high social and socioeconomical costs, access to healthcare after an injury in the justice sector is essential even after a mild injury. This study aimed to establish what currently happens when a person involved in the justice sector sustains a TBI, the strengths of current processes and improvements that could be made to facilitate access to healthcare following TBI. Semi-structured interviews with nine staff members of Ara Poutama Aotearoa (Department of Corrections) were conducted and qualitative descriptive analysis was used to capture their perspectives. There were two overarching themes identified; 1) recognition of TBI; and 2) working with individuals affected by TBI. With regards to recognition, processes for those who required hospital evaluation for moderate and severe injuries were in place, however improvements in access to services for those with milder injuries were needed. The second theme illustrated that staff perceived that processes were needed beyond initial identification, and should extend to supporting the person when working with them in everyday situations. Streamlining pathways to health practitioners within the justice sector and facilitating how corrections staff work with people who are affected by TBI may help reduce behavioural infractions and risk of reoffending. Suggestions for improving quality of care following TBI are presented as a summary at the conclusion of this thesis.